Accurate and Efficient Calculation for Full-scale Aircraft Dynamic Characteristics Based on Out-of-plane Stiffness Correction - LI Peng; WANG Yahui (Hangkong gongcheng jinzhan, 2022)
Some problems such as large number of grids,high calculation cost,large proportion of memory and slow calculation efficiency may be encountered when calculating the dynamic characteristics of full-scale aircraft structures. In order to exclude the redundant local modal from the frequency range of interest,the method of increasing the out-of-plane stiffness of the shell element is proposed,and the local modal is reduced for showing the entire modal. The accuracy and efficiency of the entire modal are verified by using a box model and a full-scale aircraft model. The results show that the out-of-plane stiffness correction method can be applied to the accurate and efficient calculation of the full-scale aircraft structure characteristics,the calculation efficiency of full-scale aircraft model is increased by more than 100 times,the file storage space is reduced by nearly 10 times,and the maximum error of the first 6-order modal frequency of full-scale aircraft is only around 4%.